Customer Satisfaction with Plastic Money in Tirupur - Tamilselvi, S.; Karpagavalli, V. (Indian Journal of Computer Science, 2018)
The development of plastic money is one of the recent phenomenon in the banking sector. Plastic money is a charge card; it is a direct charge against the limit sanctioned. It is a debt instrument issued by some specialized companies. It is one step forward towards cashless and cheque-less society. The operation is through Electronic Fund Transfer (EFT) and inter- bank network. Credit cards are the key to opening of bank accounts for daily payments by card holders. Credit card has been rightly called plastic money. The objective is to provide convenience and security. It eliminates cash transactions and protects from the danger of pick pocketing. There is usually interest free credit for 30 to 45 days.Â This paper attempts to find out the satisfaction of customers with plastic money with reference to Tirupur.